Growth response to population density in larval stage of darkling beetles (Coleoptera; Tenebrionidae) Tenebrio molitor and Zophobas atratus - Jingyoh Zaelor (2019)
© 2018 Insect farming efficiency is deterred by the complications associated with a high population density, such as competition and stress. Darkling beetles are farmable insect candidates as they are well adapted to survive at a high larval density. This study tested the effect on productivity of the larval density in two species of darkling beetle, Tenebrio molitor Linn. and Zophobas atratus Fab. Larval weight gain was measured by feeding larvae with wheat (Triticum aestivum Linn.) bran and leaves of ivy gourd (Coccinia grandis (L.) Voigt.). Larvae were also abstained to test weight loss at different larval densities. The results showed similar weight gains in both species (p = 0.7858). During abstaining periods, Z. atratus had significantly higher weight loss (p < 0.001), and Z. atratus reared at a higher larval density also had a higher weight loss (p < 0.001). Per capita weights at different densities were not significantly different in either species (T. molitor p = 0.749; Z. atratus p = 0.841). The lower survival rate in Z. atratus was assumed to be due to cannibalism which was independent of population density. T. molitor seemed to be more suitable for farming at high larval density because it had not only less weight loss during the abstaining period, but also a higher survival rate.